2009
DOI: 10.1021/ef800733h
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Capture from Flue Gas Using Palladium Nanoparticle-Decorated Substrates as Injected Sorbent

Abstract: Although the Clean Air Mercury Rule (CAMR) was recently vacated by the District of Columbia Court of Appeals, efficient mercury (Hg) capture is still an important topic for the coal-fired power plant industry. Several states have Hg emission regulations that are even more stringent than CAMR guidelines. All coals contain Hg, which is released during combustion. Significant research efforts have been made to capture this toxic element before it is released to the atmosphere where it can stay suspended and trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…[5][6][7][8][9] Nevertheless, in the case of coal gasification for power generation, Hg removal at high temperatures may lead to improvement in the thermal efficiency of IGCC system. Many researchers deeply investigated the possibility of using noble metals such as gold (Au), 10,11 silver (Ag), [12][13][14] palladium (Pd) 15,16 and platinum (Pt) 15 as efficient Hg removal sorbents. 17 These Hg removal sorbents, which show excellent performance for removal of Hg, are regenerable and are also stable for longtime operation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Nevertheless, in the case of coal gasification for power generation, Hg removal at high temperatures may lead to improvement in the thermal efficiency of IGCC system. Many researchers deeply investigated the possibility of using noble metals such as gold (Au), 10,11 silver (Ag), [12][13][14] palladium (Pd) 15,16 and platinum (Pt) 15 as efficient Hg removal sorbents. 17 These Hg removal sorbents, which show excellent performance for removal of Hg, are regenerable and are also stable for longtime operation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely accepted that the minor constituents (SOx, NOx, O 2 , and H 2 O) and fly ash play an important role in mercury reactions in flue gases from coal combustion in air [26][27][28][29]. The influence of these species on mercury oxidation was demonstrated when they were tested individually and also when they were blended in different gas compositions, although the effect was different to the sum of their individual effects.…”
Section: The Effect Of So 2 Nox and Other Constitutes On Mercury Smentioning
confidence: 99%
“…It was found that palladium-decorated carbon substrates showed excellent mercury capture capabilities, with total efficiencies greater than 90 % in laboratory-scale tests [29]. Significant research efforts have been made to capture this toxic element before it is released to the atmosphere where it can stay suspended and travel for great distances.…”
Section: Novel Sorbentmentioning
confidence: 99%
See 2 more Smart Citations